2019
DOI: 10.17221/54/2019-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Egg yolk colour and retinol concentration of eggs from laying hens fed diets containing carrot and beetroot meal

Abstract: Compounds such as pigments, antioxidants, and pro-vitamins A are found in carrots and beetroots and could increase the nutritional value of eggs when added to diets for laying hens. This research evaluated retinol concentrations and egg yolk colour with addition of freeze-dried carrot (Daucus carota L.) and beetroot (Beta vulgaris L.) meal in the diets of 240 Hisex Brown laying hens. The hens were distributed in a completely randomized design in five groups according to five experimental diets: (1) maize and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
8
12
0
Order By: Relevance
“…This clearly indicated the DFI was not affected by the RBP used on different levels. The results of this study were similar to those reported by Souza et al (2019). The researchers reported that red beet pulp added to the diets of laying hens up to 0.8% did not affect DFI.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This clearly indicated the DFI was not affected by the RBP used on different levels. The results of this study were similar to those reported by Souza et al (2019). The researchers reported that red beet pulp added to the diets of laying hens up to 0.8% did not affect DFI.…”
Section: Resultssupporting
confidence: 91%
“…The differences between the groups were found to be insignificant. The results of this study were consistent with those of Souza et al (2019), in which 0.8% red beet pulp was added to the diets of laying hens. The results of both Pettersson and Razdan (1993) and Selim et al (2013) supported our results, whereas the results reported by Kumari et al (2014) differed from those in the present study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Research results show the possibility of replacing up to 100% of corn by sorghum without causing damages on poultries performance (FAGUNDES et al, 2017;MORAES et al, 2016;SALEH et al, 2019). However, the use of sorghum causes a decrease in pigmentation of the meat and egg yolk of the birds (MOURA et al, 2010;SOUZA et al, 2015;SOUZA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%